Exploring the Impact of Acceptance and Commitment Therapy on Perceived Stress and Psychological Flexibility among Psychiatric Nurses: A Randomized Controlled Trial - Shahzadi, Shazia; Juhary, Ali; Munir, Naureen; Shah, Syed Shoaib; Farooque, Muhammad Anees (2024)
Nursing in psychiatric wards is recognized as an exceptionally stressful profession due to the challenging nature of the patients and difficulties in communication. Addressing this stress effectively can enhance nurses' overall well-being and the quality of their work. This study aimed to examine the effects of Acceptance and Commitment Therapy (ACT) on the perceived stress (PS) and psychological flexibility (PF) of nurses in psychiatric settings. Methods: Seventy nurses from the Razi Psychiatric Center in Rawalpindi were randomly assigned to either an experimental group or a control group, each comprising 35 participants. While the control group continued with their usual interventions, the experimental group participated in eight 2-hour sessions of ACT training in addition to their routine care. Assessments, including demographic information, the Perceived Stress Scale, and the Acceptance and Action Questionnaire (2nd Edition), were conducted before the intervention and one month after the final session. Results: The findings revealed a significant difference in PS (P = 0.002) and PF (P = 0.001) between the control and experimental groups, with the experimental group experiencing lower PS and greater PF. Conclusions: ACT appears to be an effective approach to reducing perceived stress and enhancing psychological flexibility, offering a potential strategy to empower nurses working in psychiatric wards.